AI Customer Service in the Digital Business World: Understanding Customer’s Thoughts on Ai-Driven Personalization in E-Commerce and Social Media - Ariel Siffrin; Raaziq Akbar Al Qarni (Artificial Intelligence Systems and Its Applications, 2025)
AI in the digital business world means the use of artificial intelligence technology to improve efficiency, productivity, and customer experience in various operational and strategic areas of a company. The Focus of this study is to see customer thoughts on the implementation of artificial intelligence in the online shopping sector. This study will be carried out in 4 different phases, including; comprised of data searching, data inputting, data processing, and editing phase. This research data was processed using the SmartPLS (Partial Least Squares) application.  The study's findings indicate that artificial intelligence (AI) has profoundly transformed the manner in which e-commerce platforms engage with consumers. The results of our study demonstrate that the provision of effective AI services can significantly improve customer satisfaction. These findings underscore the importance of implementing AI in e-commerce marketing strategies, as by understanding customer preferences and providing relevant recommendations, companies can increase customer engagement and loyalty. This study underscores the significance of AI services in enhancing customer experience and paves the way for further research that can deepen our understanding of the interaction between technology and consumer behavior in the context of e-commerce